SOCIO-ECONOMIC BACKGROUND, CAREER GOALS AND OCCUPATIONAL VALUES OF THE FUTURE MANAGERS: A COMPARATIVE STUDY - Baldev R. Sharma (Abhigyan, 2010)
This paper is based on the outcome of two studies, one carried out in 1973-74 and the other in 2007-08. The samples for the two studies consisted of MBA students. By using essentially the same questionnaire, data were collected on the following three topics: (a) socio-economic background, (b) career goals, and (c) occupational values. Though separated from each other by a gap of 34 years, the findings of the two studies are found to be remarkably similar. Through sociological analysis of the massive data, an attempt has been made in this paper to identify the factors behind the observed facts. Several suggestions are offered to make the selection of future managers more fair, just and equitable. A few suggestions are also made for sensitizing the students in order to improve their people orientation, thereby enhancing their leadership ability